Patriotism in East Asia - Kwak, Chun-hyŏk; Matsuda, Kōichirō 1961- (Political theories in East Asian context, 2015)
"Current territorial disputes between the Northeast Asian countries have stimulated a resurgence of bellicose nationalism, and threaten to upset recent efforts to achieve regional cooperation and economic integration in East Asia. Alongside this, debates over pre-1945 Japanese wartime atrocities, aggravated by still unresolved territorial disputes between Japan and its neighbours have triggered diplomatic conflicts in Japanese-South Korean relations, virulent anti-Japanese protests in China, and a dramatic increase of right-wing nationalism in Japan. Many have perceived these phenomena as inevitable corollaries, inasmuch as they regard the Northeast Asian countries as historically homogeneous and nationalistic states, and have begun to question the feasibility of the post-Cold War efforts to replace nationalism with a moderate version of civic solidarity. This book contributes to the debates surrounding patriotism and nationalism in Northeast Asia, and investigates the feasibility of non-ethnocentric patriotism in countries across the region. In doing so, it highlights the differences between Asian and Western concepts of republican patriotism via theoretical discussions of the evolving discourses on nationalism, patriotism, democracy and civic solidarity. The chapters combine theoretical discussion with historical case studies such as modern state building in late Qing Dynasty; nineteenth century Japanese political thought; and the twentieth century Korean independence movement. In turn, the contributors explore the possibilities for republican patriotism in contemporary Northeast Asia"-- Provided by publisher.